Talmud Today: A Politics of Forgetting - Dolgopolski, Sergey (Religions, 2024)
The article deals with the way in which the “theological” as the question of the Biblical G-d’s involvement in the world, as in the Talmuds, and in light of Heidegger’s thought about forgetting and forgetfulness (Verborgenheit and Vergessenheit), becomes a political question about the attitude of the Jew and Israel toward the Heimat. In Heidegger, forgetting is about beings hiding from the view rather than about a psychological or “subjective” process to which forgetting has been reduced in modernity. The Heimat hides from the persons’ life, no matter how strongly the persons strive for their Heimat “subjectively” or politically, Heidegger argues. The essay further detects a residual modernity and subjectivism in Heidegger’s concession to forgetting as only a secondary operation, a loss, in comparison to the primary, “authentic” relationship to the Heimat, which, for him, one can and should hope for. That residual modern subjectivity in Heidegger enables and necessitates a comparison with the roles forgetting plays in relationships between G-d, Israel, and the Land in the two Talmuds as, similarly to Heidegger, dealing with and working against forgetting, if not Being, then the Law of the mutual obligations between G-d and Israel. The resulting analysis distills a conundrum in the Palestinian rabbis. Delivery on Israel’s obligations towards G-d conditions Israel’s arrival to the Land, that is to say Israel’s fully successful exodus from Egypt. Yet, any clear memory of, and delivery on, these obligations, i.e., any humanly delivered testament to the law of G-d, constitutes an acute danger of forgetting masked as a would-be-certitude in the “memory” of the would-be-original law. Regaining the status of a full-fledged, never-tamed primordial power in relationships between G-d and Israel, forgetting, in the Palestinian rabbinic thought, undermines the deployment of logos as a way to formulate the Law fully. Letting the G-d in the world, logos however proves prone to reducing G-d to (a) theos, thus drawing the G-d into disappearance and forgetting. Such a counter-current to the copulation of theos with logos, the primordial power of forgetting operates even before any memory captured in words and images becomes possible. Arriving from antiquity to modernity, this counter-current continues to operate despite the currently prevalent demotion of forgetting to a subjective political act of a person or nation.